Three-dimensional urban models in complex rural environments. Proposal for automation in the historical centre of Cehegín. - Manuel Alejandro Ródenas-López; Josefina García-León; Pedro Miguel Jiménez-Vicario; Siham El Ghomari-Bakhat (Disegnare con)
Urban modelling processes are the basis for the management of Smart Cities. Automated workflows are typically used to model large portions of cities with homogeneous urban fabrics. These processes result in very simple three-dimensional models with large discrepancies with reality. However, the case of the historic centres of small cities is different due to the complexity of their urban fabric and the heterogeneity of their buildings. This paper proposes a semi-automatic supervised modelling workflow that allows the elaboration of complex urban fabric models following the CityGML standard and its levels of detail. The case study focuses on the historic centre of Cehegín (Spain). The advantage of this methodology is the use of downloadable data from public SDIs such as the Digital Cadastre (cadastral polygons) and the National Geographic Institute (LiDAR point clouds with an approximate density of 0.5 pts/m2). These data are geolocated and processed in GIS, and exported to Rhinoceros-Grasshopper3d where modelling algorithms are implemented for each level of detail, supported by statistical filters and automatic classifiers. This results in richer and more accurate models than those obtained with automatic modellers and can be used for different applications in the field of management and simulation. DOI: https://doi.org/10.20365/disegnarecon.30.2023.14